2015
DOI: 10.1016/j.chembiol.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Mechanism of Antimycobacterial Action of 5-Fluorouracil

Abstract: A combination of chemical genetic and biochemical assays was applied to investigate the mechanism of action of the anticancer drug 5-fluorouracil (5-FU), against Mycobacterium tuberculosis (Mtb). 5-FU resistance was associated with mutations in upp or pyrR. Upp-catalyzed conversion of 5-FU to FUMP was shown to constitute the first step in the mechanism of action, and resistance conferred by nonsynonymous SNPs in pyrR shown to be due to derepression of the pyr operon and rescue from the toxic effects of FUMP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 60 publications
4
75
0
Order By: Relevance
“…S6E). The delayed response was entirely consistent with the recently elucidated activity of 5-FU which, in M. tuberculosis, acts as a prodrug that must be converted into antimetabolites in order to mediate its inhibitory effects (46). Therefore, these results confirmed the utility of this simple and rapid bioluminescent reporter assay to provide early insight even into the complex MOA of a drug with demonstrated polypharmacologic activity.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…S6E). The delayed response was entirely consistent with the recently elucidated activity of 5-FU which, in M. tuberculosis, acts as a prodrug that must be converted into antimetabolites in order to mediate its inhibitory effects (46). Therefore, these results confirmed the utility of this simple and rapid bioluminescent reporter assay to provide early insight even into the complex MOA of a drug with demonstrated polypharmacologic activity.…”
Section: Resultssupporting
confidence: 70%
“…To assess their utility in providing insights into complex MOAs, we determined the luminescence profiles of the reporter strains during treatment with 5-FU. The antimycobacterial activity of this well-known anticancer drug was recently investigated through the combined application of genetic and biochemical analyses which revealed that metabolism of 5-FU produces derivatives which disrupt both cell wall homeostasis and nucleic acid biosynthesis (46). When tested in our reporter assays, 5-FU induced luminescence in all three strains at concentrations close to the MIC 99 , with the strongest signal observed in PiniB-LUX.…”
Section: Resultsmentioning
confidence: 92%
“…ThyX depletion also sensitized Mtb to idebenone with the MIC 90 shifting ~5-fold, from 125 μM to 22 μM. However, for reasons that are unclear, idebenone displayed atypical behavior in this checkerboard assay compared to 5-FU39 and E1, showing ~90% growth inhibition over an unusually large concentration range (62.5–7.8 μM) when added to thyX Tet-OFF in the presence of ATc at 6.2 ng/ml (Fig. 6B).…”
Section: Resultsmentioning
confidence: 95%
“…Molecules with whole-cell activity were then tested against a conditional knockdown mutant of Mtb H37Rv, thyX Tet-OFF, in which thyX is expressed under the control of a Tet-regulated promoter39. In this target-based whole-cell assay, compounds with ThyX-selective activity in Mtb can be identified on the basis of whether ThyX depletion confers hypersensitivity to the compound3945. As expected, the positive control, 5-FU, showed a progressive, ATc-dependent shift in MIC 90 from 3.1 μM in the absence of ATc to 0.3 μM at an ATc concentration of 6.2 ng/ml.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation